Genetic and Environmental Risk Factors for Pediatric Multiple Sclerosis - George, Ilena C.; Makhani, Naila (Journal of Pediatric Neurology, 2018)
Both genetic and environmental risk factors may contribute to risk of multiple sclerosis (MS) in children. Genetic risk factors include the presence of the human leukocyte antigen (HLA)-DRB1*1501 allele and other non-HLA single nucleotide polymorphisms. Environmental risk factors include parental smoking, low serum vitamin D levels, and prior exposure to Epstein–Barr virus. Some of these risk factors not only confer increased susceptibility to MS but may also alter the course of the disease. How different risk factors interact is a growing area of research. In this review, we examine the current literature regarding the genetic and environmental risk factors for MS in children.
Keywords: multiple sclerosis; children; environmental; genetic